2015
DOI: 10.3758/s13423-015-0857-9
|View full text |Cite
|
Sign up to set email alerts
|

The helpfulness of category labels in semi-supervised learning depends on category structure

Abstract: The study of semi-supervised category learning has generally focused on how additional unlabeled information with given labeled information might benefit category learning. The literature is also somewhat contradictory, sometimes appearing to show a benefit to unlabeled information and sometimes not. In this paper, we frame the problem differently, focusing on when labels might be helpful to a learner who has access to lots of unlabeled information. Using an unconstrained free-sorting categorization experiment… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…In doing so, researchers might also consider how different category learning challenges may alter the value of labels. For instance, while labels may generally be beneficial, their impact is likely to be reduced for more transparent categories (Vong, Navarro, & Perfors, ) or for extremely high‐dimensional spaces (Hinton & Salakhutdinov, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In doing so, researchers might also consider how different category learning challenges may alter the value of labels. For instance, while labels may generally be beneficial, their impact is likely to be reduced for more transparent categories (Vong, Navarro, & Perfors, ) or for extremely high‐dimensional spaces (Hinton & Salakhutdinov, ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, while labels may generally be beneficial, their impact is likely to be reduced for more transparent categories (Vong, Navarro, & Perfors, 2015) or for extremely high-dimensional spaces (Hinton & Salakhutdinov, 2006).…”
Section: G Ener Al Discussionmentioning
confidence: 99%
“…Second, participants did use the no-feedback trials when the underlying categories were distinct and the gap between the categories was big. However, if the underlying categories were more ambiguous and the space between the categories was small but still existing, no effect of the nofeedback trials was found (Vong, Perfors, & Navarro, 2014). Third, Kalish, Zhu, and Rogers (2015) showed that the effect of the no-feedback trials depends on the age of the participants: young children (between 4 and 6 years old) were influenced by the no-feedback trials whereas no effects were found for older children (between 7 and 8 years old).…”
Section: The Impact Of No-feedback Trials In Semisupervised Learningmentioning
confidence: 98%
“…Typically semi-supervised approaches work by making additional assumptions about the available data [89,92]. These include the smoothness assumption, i.e., samples close together in feature space are likely to be from the same class, the cluster assumption, i.e., samples in a cluster are likely to be from the same class, and the low density assumption, i.e., class boundaries are likely to be in low density areas of the feature space.…”
Section: Semi-supervised Deep Learning Strategies For Mrimentioning
confidence: 99%